A novel crane-like launch and recovery system for multiple USVs: mechanism design, control strategy, and experimental validation - D.-J. Zhang; X.-H. Xiao; G. Li; C.-X. Li; Y. Yang (Mechanical Sciences)
To enhance safety in offshore operations and minimize modifications to the mother ship, an autonomous crane-like launch and recovery (LAR) system is essential for deploying and retrieving uncrewed surface vehicles (USVs). Traditional crane-like LAR systems are typically designed for handling a single USV, limiting operational efficiency. This paper proposes a novel crane-like LAR system capable of launching and recovering multiple USVs, improving efficiency and convenience. The system consists of a foldable crane arm, three floating brackets, two configuration control mechanisms (CCMs), and a lifting and lowering mechanism. The design and analysis of the foldable crane arm and CCMs are presented in detail. Furthermore, a vision-guided autonomous docking and recovery control strategy is proposed to enable autonomous docking operations. To validate the system, a prototype was developed, and comprehensive experiments were conducted. The results demonstrate that the system successfully recovers three USVs with smooth and stable motion.